Dilution Effects of Highly Concentrated Dimethyl Carbonate-Based Electrolytes with a Hydrofluoroether on Charge/Discharge Properties of LiNi0.8Co0.1Mn0.1O2 Positive Electrode. Issue 16 (1st January 2019) - Cao, Ziyang; Haruta, Masakazu; Doi, Takayuki; Inaba, Minoru
Abstract : In highly concentrated LiBF4 /dimethyl carbonate (DMC) electrolyte, Ni-rich LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) positive-electrode exhibited a good cycle performance and the crack formation in NCM811 particles was remarkably suppressed. However, the high concentration causes some problems, such as a high viscosity, a low ionic conductivity and a high cost. To solve these problems, we chose 1, 1, 2, 2–tetrafluoroethyl 2, 2, 3, 3–tetrafluoropropyl ether (HFE) to dilute the concentrated LiBF4 / and LiPF6 /DMC systems. The cycle performance of NCM811 electrode remarkably deteriorated in 0.96 mol kg −1  LiBF4 /DMC+HFE (1:2 by volume). Raman spectra indicated that the fraction of free DMC increased in the diluted electrolyte, which led to instability against oxidation. However, in the LiPF6 /DMC system, the fraction of free DMC had rarely increased after diluted with HFE. The diluted electrolyte showed a high stability against oxidation comparable to the nearly saturated electrolyte, and the NCM811 electrode showed an excellent cycle performance.